Occupancy Detection Using a Frequency-Modulated Phase- and Self-Injection-Locked (FMPSIL) Radar and Two-Stage Generalized Likelihood Ratio Test (GLRT) Algorithm - Shih, Ju-Yin; Zhong, Ji-Xun; Wang, Fu-Kang (IEEE transactions on microwave theory and techniques, 2024)
This study proposed a frequency-modulated phase- and self-injection-locked (FMPSIL) radar for occupancy detection. Compared to the conventional range-Doppler map, which performs occupancy detection by obtaining the vital sign of the subject using 2-D fast Fourier transform (2-D-FFT), this study proposed a two-stage generalized likelihood ratio test (GLRT) algorithm to overcome the leakage problem in the spectrum and increase occupancy detection accuracy. The use of the probability density function (pdf)-based GLRT analysis in the time domain reduced the required computational cost and observation time. To demonstrate the feasibility of the proposed two-stage GLRT algorithm, experiments were conducted for a 600-min dataset in a cluttered environment, the algorithm achieved a detection accuracy of 97.32% at an observation time of 5 s for a single moving target, and multitarget occupancy detection was also achieved.